Flipped Classroom Learning Innovation as an Attempt to Strengthen Competence and Competitiveness of Students in the 4.0 Industrial Revolution Era - Halimatus Syakdiyah; Basuki Wibawa; Zulfiati Syahrial (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Industrial era 4.0, is an era of challenges and hopes for the world of education. In this disruptive era, education must be able to improve and innovate in order to survive and continue to face the challenges of the times. The world of education has great hopes in the era of digitalization in an effort to facilitate the achievement of educational goals. This article wants to provide an overview of flipped classroom learning strategies in the 4.0 era with all the challenges. Based on the results of research that have been carried out proven flipped classroom strategy can effectively improve student chemistry learning outcomes. The research was carried out through a quantitative approach using an experimental method with 2x2 Treatment by Level design on chemistry subjects on Thermochemistry subject matter and rate of reaction. Thermochemistry and rate of reaction are the subjects with the lowest achievement in the 2016 National Examination (UN) results, which is 27% in Thermochemistry and 31% in the rate of reaction. Therefore, it is necessary to innovate learning strategies that are expected to be appropriate and can improve student learning outcomes in this 4.0 era. Then how should flipped classroom learning strategies be packaged in this disruptive era?